Analisis Pengaruh Citra Merek Dan Kepercayaan Terhadap Loyalitas Pelanggan Aqua Di Basa Swalayan Kabupaten Pemalang - Devfi Indriana; Yunus Handoko; Widi Dewi Ruspitasari (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2022)
AQUA is the market leader in the bottled drinking water industry, but Aqua has a problem with customer loyalty, this is shown by AQUA's customers being willing to buy other products when bottled drinking water with the AQUA brand cannot be found. Aqua's position is also increasingly threatened by the arrival of competitors who continue to innovate and improve their quality. To be able to continue to survive as a market leader in the bottled drinking water industry, AQUA must keep its customers from switching to other brands. This study aims to determine the effect of Brand Image and Brand Trust on AQUA customer loyalty in Basa Swalayan Pemalang Regency. The independent variables in this study are Brand Image and Brand Trust, while the dependent variable is customer loyalty. The population in this study were AQUA customers at Basa Swalayan Pemalang Regency, the number of research samples was 100 respondents, the analytical tool used in this study was multiple linear regression, Based on the results of the study, it is known that brand image and brand trust have a significant effect on AQUA customer loyalty at Basa Swalayan Pemalang Regency Keywords: Customer Loyalty, Brand Image and Brand Trust